Developing An English Writing Skills of English Study Program Students in Semester - 2 of PGRI Indraprasta University. - Rasul, Tarmizi; Suwandi, Sahri; Nursitti, Sjafly (STKIP PGRI Tulungagung, 2025)
The preliminary study revealed that 90% of the university students were not able to write in English well. There were some problems which made the semester-2 learners of the English Study Program of PGRI Indraprasta University unable to write in English. One of them was a method used by English teachers to teach writing. The preliminary study showed that 90% of the students were not able to write in English. While the objective of this study was to make learners write in English easily. The method used in this study to make learners was the oral questioning method or oral questioning guide in L1 (OQIGIL) since it could enrich the students vocabulary and improve their grammar understanding. There were two ways. First, Enrich the students' vocabulary. Second, change the way to teach grammar, especially tenses. The way to teach tenses should use the family term since a sentence is like a family. There was a subject that was called a mom. Mom consisted of two. Mom who had a ring was called “s” namely she, he it. This mom “she, he, it influenced a verb which followed it. For example, she never goes to school since she moved to another city. The second mom did not need “ s” as a symbol of the ring any more since this mom was busy with her children. This mom is “they, we, I, you.” This subject did not influence a verb which followed it. For example, the children usually go to school. While my father had two. First a sibling father who had an action because he had moved every day to make a living for his family. Second, a step father which consisted of “is, am, are, was, were, be and been. The role of step father was to replace the sibling father if he had passed away. While to enrich vocabulary, the researcher used a short story which was translated into his first language.